2014
DOI: 10.15517/rbt.v62i0.15922
|View full text |Cite
|
Sign up to set email alerts
|

Monitoreo en aguas cercanas al área marina protegida en la costa de Granada, Caribe Oriental: cobertura bentónica y poblaciones de peces

Abstract: Grenada is highly dependent on coral reefs as a source of food and to support tourism. Local and global environmental stressors threaten these reefs. Legislation was created for this MPA in 2001, permanent mooring buoys were deployed in 2009 and enforcement of fishing restrictions began in 2010. Initiatives to address point and nonpoint source pollution from the land have recently begun, aimed at reducing stress on reef area. This study documents benthic cover and fish populations associated with reefs in a Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…A few species, in particular M. mirabilis, A. lamarcki and P. astreoides, however, appear to be more resilient and their decrease in cover and abundance was less distinct (Figure 4, Table S2). This is confirmed by observations throughout the Caribbean (Green et al, 2008;Anderson et al, 2014;Perry et al, 2015). Nevertheless, these species seem to decline when the overall coral cover in the quadrat was substantially reduced.…”
Section: Discussionsupporting
confidence: 82%
“…A few species, in particular M. mirabilis, A. lamarcki and P. astreoides, however, appear to be more resilient and their decrease in cover and abundance was less distinct (Figure 4, Table S2). This is confirmed by observations throughout the Caribbean (Green et al, 2008;Anderson et al, 2014;Perry et al, 2015). Nevertheless, these species seem to decline when the overall coral cover in the quadrat was substantially reduced.…”
Section: Discussionsupporting
confidence: 82%
“…This lack of acroporids is attributed to their region-wide decline since the 1980s, with their near absence being noted in the nearby Tobago Cays in 1999 [35,36]. The percent coral cover values obtained in the present study for Grenada are slightly higher than those reported in recently published literature for the same study sites [20,21]. No significant differences in coral cover were detected between the islands.…”
Section: Discussioncontrasting
confidence: 61%
“…Ocean surgeonfish grazing increased growth of P. astreoides, but parrotfish have no impact [52]. Herbivorous fish biomass in Grenada and Carriacou is 'poor' [53] and herbivorous invertebrates, such as Diadema antillarum, are also now largely absent from reef communities in Grenada [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation